Effectiveness of Eco Theology Based Arabic Posters in Enhancing Reading Literacy in Mahārat al-Qirā’ah - Rita Zahara Kamsir; Syahrur Ramli; Rahmatia Safitri; Zulpina Zulpina; Meisil Yanda; Suryati Suryati; Tri Rifni Rosita (Yayasan Darussalam Bengkulu, 2025)
This research aims to integrate specific eco-theological values into Mahārat al-Qirā’ah (reading skills) through strategically designed visual media. By embedding these themes, the study seeks to transform language learning from a mechanical exercise into a transformative ethical experience that fosters sustainable behavior. The escalating global climate crisis necessitates an urgent pedagogical shift within Islamic higher education to address stagnant environmental literacy among students. Traditional Arabic curricula often exacerbate this by relying on classical materials that lack contextual relevance. A mixed-methods research design was employed at State Islamic University in Batusangkar to capture quantitative literacy shifts and qualitative experiences. The study involved 119 second-year Islamic Education (PAI) students from the 2024/2025 academic years, selected by purposive sampling. Data collection utilized pre-tests and post-tests alongside interviews and student reflections. Quantitative analysis was performed using T-tests and N-gain scores. The results of eco-theological posters significantly enhance student performance across all evaluated dimensions. Vocabulary Recognition and Literal Comprehension showed steady improvements of 41.1% and 42.2%, respectively. However, higher-order skills experienced a dramatic surge: Inferential Reading scores rose by 69.5%, while Ethical Synthesis demonstrated a remarkable 113.0% improvement. N-gain analysis confirmed high effectiveness, particularly in Ethical Synthesis, which achieved a score of 0.75. These findings reflect a successful transition from foundational decoding to advanced value-based interpretation. Posters act as a